Analisis Manajemen Risiko Framework COBIT 2019 Dengan Metode AHP (Studi Kasus: PT Apro Global Solusi) - Rohman, Fredi Muhammad; Susanto, Agung Budi; Waskita, Arya Adhyaksa (Jurnal Ilmu Komputer, 2023)
PT Apro Global Solusi (AGS) is an information technology company that helps customers achieve their business goals by providing the best consulting in its class. Problems that occur at PT AGS such as data leaks, suboptimal governance make it a reproach for the occurrence of risks in the IT division, This research will use the Cobit 2019 framework and the AHP (Analytic Hierarchy Process) method to make decisions. The research object will focus on risk management in PT AGS IT division so that it has good control in IT risk management. Cobit 2019 implementation and the AHP method can be implemented properly so that AGS can set standards for good governance and minimize risks that will occur, with decision makers the AHP method can be a reference for the IT Division to look for flaws that can cause risks and create IT divisions PT Apro Global Solusi has good standards.